Kepastian Hukum Transaksi Direksi Yang Memuat Benturan Kepentingan Ditinjau Dari Good Corporate Governance (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Directors have a crucial role in the company, with the potential for actions that are not in accordance with corporate governance that can be detrimental and cause conflicts of interest, threatening the company's growth. In this context, Good Corporate Governance becomes crucial as a supervision to prevent detrimental actions. This article discusses Directors' Transactions involving Conflicts of Interest and legal certainty of director actions. The research uses normative juridical methods, with a statutory regulatory approach as the basis. Actions or transactions with a conflict of interest are considered not to be a legal problem if they are carried out in good faith, in accordance with KEP-412/BL/2009. However, a different view emerges from the principles of good corporate governance which suggest avoiding transactions with conflicts of interest. The research conclusion confirms that directors, as holders of trust, cannot be held responsible for losses if they act in good faith. Although the law allows transactions with conflicts of interest, the principles of good corporate governance emphasize the importance of avoiding actions that involve conflicts of interest in order to maintain the principles of good corporate governance.